Museums and the history of computing : objects, narratives and practice - Natale, Simone, 1981-; Foti, Petrina; Parry, Ross (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"Museums and the History of Computing examines the critical role that cultural organisations, such as museums and galleries, play in shaping 'digital heritage': the cultural heritage surrounding computer technology. Focusing on digital technologies as objects and practices that museums collect, exhibit, and preserve for the future, this book highlights how and why museums play a crucial role in preserving the rich heritage of the digital world, constructing powerful narratives that help make it relevant to the public. It demonstrates that the museum can be a powerful means of safeguarding and interpreting ephemeral and continually changing digital technology, offering new pathways for rethinking the very meaning of digital objects and practices in contemporary societies. It provides practices and strategies for the preservation and exhibition of computing artefacts and ways to accommodate and respond to narratives about histories of computing that circulate in the public arena. Bringing together leading museum and university researchers and practitioners, and mobilizing cross-cutting debates and approaches in areas such as museum studies, cultural heritage, history of technology, anthropology, and media studies, this book challenges us to think critically about what 'digital' is when examined not only as a tool, but as a cultural object deserving of attention and a place within the museum. Museums and the History of Computing is for museum studies students and researchers as well as museum practitioners - especially those with an interest in digital technology and heritage. It will be of interest to researchers and students interested on histories of computing and digital media and on digital media studies"--
PART I: Lives narrated through computer history -- Unseen connections: Exhibiting the global stories of cellular telephony at the Smithsonian's National Museum of Natural History / Joshua Bell -- Lives on shelves: Constructing histories of computing in the museum store / Simona Casonato -- Provocation no. 1: Imparting the history of 'intangible things' / Mai Sugimoto -- PART II: The life inscribed on computer technology -- Restorations, replicas, and emulations in a museum of computing / Martin Campbell-Kelly & Mark Priestley -- Social media enters the museum: Collecting WeChat at the Victoria & Albert Museum / Corinna Gardner, Juhee Park & Natalie Kane -- Provocation no. 2: All of this belongs to us / Andrea Lipps -- PART III: Living computing history collections -- Mediators, media and meaning: Curating digital objects at the science museum / Tilly Blyth & Rachel Boon -- Unsettling the narrative: Quantum computing in museum environments / Petrina Foti -- Provocation no. 3: Why is the computer different? / Kimon Keramidas -- PART IV: Lived practice of computing history -- The CHM stack: Experimentation for digital and computing heritage / David Brock, Hansen Hsu, Marc Weber & Dag Spicer -- Beyond Point and Click: Calling out expediency in museums' histories of computing / Lisa McGerty -- Provocation no. 4: Decolonizing Computing Histories in Museums / Lara Ratnaraja.
"Routledge Focus" -- from cover.
Keywords: Science museums; Museum exhibits; Digital preservation -- History; Computer science -- History; Information technology -- History; Electronic data processing -- History; Digital preservation; Museums -- Data processing; LANGUAGE ARTS & DISCIPLINES / Library & Information Science; SOCIAL SCIENCE / Archaeology